Strategic Contribution of a Business Process to Company's Performance - Brin, P. V.; Prokhorenko, Olena; Nehme, M. N.; Trabulsi, H. (University of Tehran, 2020)
The study is aimed at assessing the strategic importance of a business processes for achieving sustainable competitive advantage, therefore, in this article the theoretical approach for measuring the strategic contribution of a business process to an enterprise’s business system is presented. For evaluating of a business process strategic importance the study proposes the system of economic and managerial indicators, which includes the process’ contribution to the added value, its compliance to critical success factors, and its organizational involvement. Сombining these three indicators into one integral allows it to be used in different types of matrix analysis to make decisions on improving of a company’s business system.
Keywords: business processes' significance; strategic contribution; organizational involvement; added value; critical success factors; assets